Effects of orthodontic forces on pulp tissue - Pinandi Sri Pudyani (Universitas Airlangga, 2006)
Numerous researches on pulp tissue changes caused by orthodontic forces have been performed, among others are: pulp angiogenesis, pulp tissue respiration rate, alkaline phosphatase and aspartate aminotransferase enzyme activities; micro vascular response inside the pulp and the effect of dental movement i.e. extrusion, intrusion, and torque. The result is still controversial, as some researchers claim that orthodontic force has a negative effect, others deny by saying there is no such effect on pulp tissue.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />